(untitled) (Research, Society and Development, 2020)
The weather and the conditions to which animals are exposed in the pre-slaughter period have a marked impact on the quality of the meat, an aspect that becomes more important due to the recent climate and the forecasts of increase in global warming. In this context, the present review aims to address the main qualitative characteristics of the carcass and the sheep meat, seeking to relate them to the effects of weather and thermal stress in pre-slaughter. Among the climatic variables, high temperature and high air humidity, in private, have significant effects on the quality of meat. These climatic conditions, when in high degrees, cause a physiological imbalance that has a direct effect on muscle glycogen stores, responsible for post-mortem biochemical reactions, affecting the physical, chemical and sensorial characteristics of meat. It is necessary to adapt management practices and facilities aiming, at first, to obtain better conditions of animal welfare in the face of the stressful climatic conditions, thus favoring the obtaining of carcasses and meats with favorable sensorial attributes from the viewpoint of consumers.